THE ROLE AND IMPORTANCE OF THE MOVEMENT AT THE AGE OF CHILDHOOD AND ADOLESCENCE (University Arena, 2025)
Background. The motor development of children and adolescents, manifested through their physical aptitude, is a complex of genetic, somatic, motor and behavioral characteristics. These components are influenced by social factors and income and education levels in the family, occupation of parents, place of residence, ethnicity, number of family members. These factors, combined with socio-economic conditions and lifestyle, can indirectly alter the motor development of young people. Hypothesis. In the study we carried out we wanted to find out whether somatic development of children and adolescents contribute to the harmonious development of body and also if living standards influence the development of motor skills. Objectives. We plan to get out and argue for student participation in sports leisure. Research methods: survey (based on questionnaires); observation method, statistical and mathematical; graphic method. Results. Self-employment practice physical exercise is part of the favorite activities of students and is a permanent means, efficient and pleasant leisure. Conclusions. Physical exercise in leisure time is influenced by the wealth of the family and of health. Preferences investigated students heading for activities such as: aerobics and maintenance, tennis, jogging, swimming, volleyball, karate, cycling etc.